DIFFERENCES IN FOOD INTAKE (ENERGY, PROTEIN, FAT AND CARBOHYDRATES) IN CHILD WASTING BY GIVING COOKIES OF PURPLE SWEET POTATO AND TEMPEH FLOUR - Fitria Mushollini; Harsono Salimo; Lilik Retna Kartika Sari (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2023)
Wasting is a malnutrition condition attributable to insufficient food intake and/or disease. Poor quality and quantity nutrition in food intake is particular concern, especially for child wasting. One of the efforts to deal of child wasting is by providing nutrient-rich supplementary foods such as cookies. Cookies of purple sweet potato and tempeh flour have nutritional value of protein (8.06-22.31%) and carbohydrates (63.85-82.42%). The aim of study was to analyze differences in food intake (energy, protein, fat and carbohydrates) in child wasting by giving cookies of purple sweet potato and tempeh flour. The design of this study was quasi-experiment used a pre-posttest design with a controlled group. The study consisted of a control group (100% purple sweet potato cookies), K1 (90% purple sweet potato: 10% tempeh flour) and K2 (80% purple sweet potato: 20% tempeh flour). The intervention for 30 days. The analyze of data used were paired t-test and One-Way Anova. The results found that there was an increase in food intake (energy, protein, fat and carbohydrates) before and after giving cookies of purple sweet potato and tempeh flour and it was statistically significant. There was a significant difference food intake in each group after intervention by cookies (p<0.05). Intervention with cookies of purple sweet potato and tempeh flour could be the alternative to increase food intake in child wasting.